Pengaruh Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Karyawan: Studi Kasus PT Sucofindo Palembang Indonesia - Muhammad Idris; Dian Novita Sari (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2019)
The problem in this study is whether there is an influence of leadership and work discipline on the employees’ performance of PT.Sucofindo Palembang City. This research includes associative research. The sample in this study were 88 respondents, with propotionate random sampling analysis technique. The data used were primary data and secondary data. Data collection method through questionnare. Analysis techniques using multiple linear regression analysis, F test (Simultaneoys) and t test (partial) and determination coeffiecient. The results show that there is influence of leadership and work discipline on the performance of PT.Sucofindo Palembang City.